Role of Serum Carcinoma Embryonic Antigen (CEA) Level in Localized Pancreatic Adenocarcinoma: CEA Level Before Operation is a Significant Prognostic Indicator in Patients With Locally Advanced Pancreatic Cancer Treated With Neoadjuvant Therapy Followed by Surgical Resection: A Retrospective Analysis. Issue 5 (24th May 2022) - Kato, Hiroyuki; Kishiwada, Masashi; Hayasaki, Aoi; Chipaila, Jackson; Maeda, Koki; Noguchi, Daisuke; Gyoten, Kazuyuki; Fujii, Takehiro; Iizawa, Yusuke; Tanemura, Akihiro; Murata, Yasuhiro; Kuriyama, Naohisa; et al.
Abstract : Objective: The aim of the study was to identify the prognostic factors before neoadjuvant chemoradiotherapy (NCRT) in the patients with localized PDAC. Furthermore, to identify the post-surgical survival predictors of patients with LAPC. Summary of background data: Surgical resection may occupy an important position in multimodal therapy for patients with LAPC; however, its indication and who obtains the true benefits, is still uncovered. Materials and Method: From 2005 to 2017, 319 patients with localized PDAC who underwent NCRT were reviewed. Only 159 patients were diagnosed with LAPC, of these 72 patients underwent surgical resection. We examined the pre-NCRT prognostic factors in the entire cohort and conducted further subgroup analysis for evaluating the post-surgical prognostic factors in LAPC patients under the pretext of favorable local tumor control. Results: In the entire cohort, pre-NCRT CEA value was recognized as the most significant prognostic indicator by multivariate analysis. In the 72 LAPC patients who underwent surgical resection, only high CEA level was identified as an independent dismal prognostic factor before surgery. At the cut-off value: 7.2ng/mL, survival of the 15 patients whose CEA value >7.2 ng/mL was significantly unfavorable compared to those of 57 patients with <7.2 ng/mL: Median disease-specific survival time: 8.0 versus 24.0 months (P < 0.00001). Moreover, the median recurrence-free survival time of the high CEA group was only 5.4 months and there was no 1-year recurrence-free survivor. Conclusions: CEA before NCRT is a crucial prognostic indicator for localized PDAC. Moreover, LAPC with a high CEA level, especially more than 7.2 ng/mL, should still be recognized as a systemic disease, and we should be careful to decide the indication of surgery even if tumor local control seems to be durable.